Risk factors of colorectal cancer recurrences after radical surgery - Mikėnas, Saulius; Liaudginas, Tomas; Paškonis, Marius; Poškus, Eligijus; Jurgaitis, Jonas; Strupas, Kęstutis (Lietuvos chirurgija, 2017)
Introduction Each year about 1,500 cases of colorectal cancer is diagnosed in Lithuania and the incidence of this disease is increasing every year. Radical surgery removal is the first choice treatment of the cancer that presents the best long-term results. Recurrence of the disease after surgery is difficult to diagnose due to the lack of clinical symptoms and insufficient sensitivity of imaging study. The aim of the study was to evaluate risk factors for second-look surgery of colorectal cancer following complete cytoreductive surgery. Materials and methods Between 2011 and 2014 in 321 cases radical T3-T4 stage colorectal cancer surgery was performed. 208 of 321 patients were involved to study. In a single centre retrospective study we analyzed operation records and pathophysiological protocols. Results A total 34 (16.3%) patients had recurrence of the disease in 1-4 year. In 15 (26,8%) T4 stage and 19 (12.5%) T3 stage cases colorectal cancer relapsed (p=0,013). Lymph node invasion impacts recurrence: N0 – 10 (9.8%), N1 – 12 (18.2%) N1, N2 – 12 (30%) (p=0.012). 7 (46.7%) occlusive colorectal cancer cases had recurrence (p=0.003). This study does not show statistical significant difference between the recurrence of disease and histological subtype, tumor perforation or location. 5-year predicted survival with recurrence is 0% and without – 24.65%. Conclusions After resection of the primary tumor it is important to follow up these patients, in order to prevent them from recurrence of disease. Patients, who are at higher risk group of developing peritoneal carcinomatosis, should be considered performing a second-look surgery with CRS and HIPEC.